Prevalence, detection and associations of depression in Australian dialysis patients. (October 2019) - Kwan, Elaine; Draper, Brian; Harvey, Samuel B; Endre, Zoltan H; Brown, Mark A
Objective: Depression in dialysis patients is often undetected despite associations with poor outcomes. The aim was to determine the prevalence and associations of depressive symptoms and physician recognition of depression within a typical Australian dialysis population. Method: A cross-sectional study examined haemodialysis and peritoneal dialysis patients of two hospitals in Sydney. Participants were screened for depression using the Hospital Anxiety and Depression Scale (HADS). Results: One hundred and ten patients completed the HADS. Subjects had a mean age of 63.7 years, 37% from a culturally and linguistically diverse background, and median dialysis duration of 2 years. Forty-one per cent of participants had significant depressive symptoms, of whom 42% had been diagnosed with depression by their clinicians. After adjustment for sociodemographic factors, having >10 medications prescribed, >3 hospitalisations in the last 12 months, and a history of depression were associated with depression. Conclusion: Depressive symptoms are prevalent in Australian dialysis patients. Robust evidence is needed on the effectiveness of treatments for depression in changing outcomes in chronic kidney disease.